Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the equation \( x^4 + 6x^2 + 5 = 0 \) using substitution, we'll follow these steps:
1. Substitute Variables: First, let's make a substitution \( u = x^2 \). This allows us to transform the given equation into a simpler quadratic form.
2. Rewrite the Equation: Substitute \( u = x^2 \) into the original equation:
[tex]\[ x^4 + 6x^2 + 5 = 0 \implies u^2 + 6u + 5 = 0 \][/tex]
3. Solve the Quadratic Equation: Next, we solve the quadratic equation \( u^2 + 6u + 5 = 0 \) for \( u \). This can be done using the quadratic formula \( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) where \( a = 1 \), \( b = 6 \), and \( c = 5 \).
[tex]\[ u = \frac{-6 \pm \sqrt{6^2 - 4 \cdot 1 \cdot 5}}{2 \cdot 1} \][/tex]
[tex]\[ u = \frac{-6 \pm \sqrt{36 - 20}}{2} \][/tex]
[tex]\[ u = \frac{-6 \pm \sqrt{16}}{2} \][/tex]
[tex]\[ u = \frac{-6 \pm 4}{2} \][/tex]
This gives us two solutions:
[tex]\[ u = \frac{-6 + 4}{2} = \frac{-2}{2} = -1 \quad \text{and} \quad u = \frac{-6 - 4}{2} = \frac{-10}{2} = -5 \][/tex]
4. Return to Original Variables: Now, reverse the substitution to return to the variable \( x \). We have \( u = x^2 \), so we need to solve the equations \( x^2 = -1 \) and \( x^2 = -5 \) for \( x \).
- For \( x^2 = -1 \):
[tex]\[ x = \pm \sqrt{-1} = \pm i \][/tex]
- For \( x^2 = -5 \):
[tex]\[ x = \pm \sqrt{-5} = \pm i\sqrt{5} \][/tex]
5. Collect all Solutions: Combining these, the solutions to the original equation are:
[tex]\[ x = \pm i \quad \text{and} \quad x = \pm i\sqrt{5} \][/tex]
So, the solutions of the equation \( x^4 + 6x^2 + 5 = 0 \) are \( x = \pm i \) and \( x = \pm i\sqrt{5} \). Thus, the correct answer from the given options is:
```
[tex]$x= \pm i$[/tex] and [tex]$x= \pm i \sqrt{5}$[/tex]
```
1. Substitute Variables: First, let's make a substitution \( u = x^2 \). This allows us to transform the given equation into a simpler quadratic form.
2. Rewrite the Equation: Substitute \( u = x^2 \) into the original equation:
[tex]\[ x^4 + 6x^2 + 5 = 0 \implies u^2 + 6u + 5 = 0 \][/tex]
3. Solve the Quadratic Equation: Next, we solve the quadratic equation \( u^2 + 6u + 5 = 0 \) for \( u \). This can be done using the quadratic formula \( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) where \( a = 1 \), \( b = 6 \), and \( c = 5 \).
[tex]\[ u = \frac{-6 \pm \sqrt{6^2 - 4 \cdot 1 \cdot 5}}{2 \cdot 1} \][/tex]
[tex]\[ u = \frac{-6 \pm \sqrt{36 - 20}}{2} \][/tex]
[tex]\[ u = \frac{-6 \pm \sqrt{16}}{2} \][/tex]
[tex]\[ u = \frac{-6 \pm 4}{2} \][/tex]
This gives us two solutions:
[tex]\[ u = \frac{-6 + 4}{2} = \frac{-2}{2} = -1 \quad \text{and} \quad u = \frac{-6 - 4}{2} = \frac{-10}{2} = -5 \][/tex]
4. Return to Original Variables: Now, reverse the substitution to return to the variable \( x \). We have \( u = x^2 \), so we need to solve the equations \( x^2 = -1 \) and \( x^2 = -5 \) for \( x \).
- For \( x^2 = -1 \):
[tex]\[ x = \pm \sqrt{-1} = \pm i \][/tex]
- For \( x^2 = -5 \):
[tex]\[ x = \pm \sqrt{-5} = \pm i\sqrt{5} \][/tex]
5. Collect all Solutions: Combining these, the solutions to the original equation are:
[tex]\[ x = \pm i \quad \text{and} \quad x = \pm i\sqrt{5} \][/tex]
So, the solutions of the equation \( x^4 + 6x^2 + 5 = 0 \) are \( x = \pm i \) and \( x = \pm i\sqrt{5} \). Thus, the correct answer from the given options is:
```
[tex]$x= \pm i$[/tex] and [tex]$x= \pm i \sqrt{5}$[/tex]
```
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.